2017
DOI: 10.1101/126011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polymorphisms in the yeast galactose sensor underlie a natural continuum of nutrient-decision phenotypes

Abstract: In nature, microbes often need to “decide” which of several available nutrients to utilize, a choice that depends on a cell’s inherent preference and external nutrient levels. While natural environments can have mixtures of different nutrients, phenotypic variation in microbes’ decisions of which nutrient to utilize is poorly studied. Here, we quantified differences in the concentration of glucose and galactose required to induce galactose-responsive (GAL) genes across 36 wild S. cerevisiae strains. Using bulk… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 92 publications
(121 reference statements)
1
9
0
Order By: Relevance
“…A previous study identified GAL3 as an important genetic determinant for this decision: The concentration ratio at which cells turn GAL expression ON differs between strains harboring different natural alleles of GAL3 (Lee et al, 2017). We asked if this variation, visible in the steady-state exposure to both glucose and galactose, was correlated with the variation observed on the dynamics of network induction upon exposure to galactose only.…”
Section: Variation In Induction Dynamics Is Consistent With Variationmentioning
confidence: 93%
See 3 more Smart Citations
“…A previous study identified GAL3 as an important genetic determinant for this decision: The concentration ratio at which cells turn GAL expression ON differs between strains harboring different natural alleles of GAL3 (Lee et al, 2017). We asked if this variation, visible in the steady-state exposure to both glucose and galactose, was correlated with the variation observed on the dynamics of network induction upon exposure to galactose only.…”
Section: Variation In Induction Dynamics Is Consistent With Variationmentioning
confidence: 93%
“…We asked if this variation, visible in the steady-state exposure to both glucose and galactose, was correlated with the variation observed on the dynamics of network induction upon exposure to galactose only. We chose four strains that showed different decision thresholds because of different GAL3 alleles (Lee et al, 2017; Fig 5B), and we monitored their dynamics of induction at three different concentrations of galactose (with no glucose). We then used our model to assign q Gal3 and K Gal parameter values to each strain.…”
Section: Variation In Induction Dynamics Is Consistent With Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…We next sought to determine if natural isolates have genetic variants that independently 5 affect the rheostat and the switch. We have shown that there is natural variation in both the rheostats and switch (24,25). We chose two isolates, S288C and DBVPG1106 ( Fig.…”
Section: Main Textmentioning
confidence: 98%